SUMO E3 ligase PIAS1 is a potential biomarker indicating stress susceptibility. (October 2020) - Lin, Hsiao-Yun; Liu, Yu-Shu; Huang, Ching-Ya; Cathomas, Flurin; Liu, Kalena; Wang, Jun; Cheng, Han-Tsung; Lai, Sheng-Wei; Liu, Yu-Ching; Chen, Chao-Jung; Lin, Chingju; Lu, Dah-Yuu
Highlights: Alter PIAS1 expression in hippocampus impacts social behavior. Disrupt PIAS1-GR interaction in hippocampus is associated with maladaptive stress response. PIAS1 plays a critical role in mediating stress susceptibility by post-translational modification of GRs. Abstract: Prior studies suggest that individual differences in stress responses contribute to the pathogenesis of neuropsychiatric disorders. In the present study, we investigated the role of small ubiquitin-like modifier (SUMO) E3 ligase protein inhibitor of activated STAT1 (PIAS1) in mediating stress responses to chronic social defeat stress (CSDS). We found that mRNA and protein levels of PIAS 1 were decreased in the hippocampus of high-susceptibility (HS) mice but not in low-susceptibility (LS) mice after CSDS. Local overexpression of PIAS1 in the hippocampus followed by CSDS exposure promoted stress resilience by attenuating social avoidance and improving anxiety-like behaviors. Viral-mediated gene transfer to generate a conditional knockdown of PIAS1 in the hippocampus promoted social avoidance and stress vulnerability after subthreshold microdefeat. HS mice displayed decreased levels of glucocorticoid receptor (GR) expression, and GR SUMOylation in the hippocampus was associated with stress vulnerability. Furthermore, cytokine/chemokine levels were changed predominantly in the hippocampus of HS mice. These results suggest that hippocampal PIAS1 plays a role in the regulation of stress susceptibility by post-translational modification of GRs.